Teen fathers : getting involved - Endersbe, Julie K. (Mankato, Minn. : LifeMatters, 2000)
Discusses problems and dilemmas faced by teenage males when they become fathers and identifies options and solutions available to them.
Includes bibliographical references (p. 61) and index.
Keywords: Teenage fathers -- Juvenile literature; Teenage fathers